A language for the Common Digital Space of Scientific Knowledge ontology representation - N. E. Kalenov; A. N. Sotnikov (Учёные записки Казанского университета: Серия Физико-математические науки, 2025)
A language for describing the Common Digital Space of Scientific Knowledge (CDSSK) ontology was proposed. Tailored to the evolving digital knowledge space with its high dynamics in the emergence of new scientific findings and the presence of various types of objects with multilevel attributes and relations, it incorporates the principles of the Ontology WEB Language but focuses on multilevel attributes of objects and named relations of various structures. Based on the analysis of the CDSSK objects, their attributes were classified, as well as the relations between them. Five types of attributes (first- and second-kind simple attributes, first- and second-kind composite attributes, and attributes “as relations”) and three classes of relations (universal, quasi-universal, and specific) were singled out. Within the classes, each relation can be “simple” or composite and falls into one of three distinct kinds. The language uses unified guides and dictionaries in JSON format. Its syntax is built around a system of unique names derived according to fixed mnemonic rules, which uniquely identify the type of the element and its relation to a specific object from the name structure. The language applicability was illustrated with examples.